PEMIKIRAN SYEKH NAWAWI AL-BANTANI TENTANG PENDIDIKAN KARAKTER: ANALISIS KRITIS DALAM KONTEKS KURIKULUM MERDEKA - Fradana, Heru (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2024)
Abstract This study aims to compare moral education according to Syekh Nawawi with character education in the strengthening project of the Pancasila Student Profile (P3) and the Rahmatan lil 'Alamin Student Profile (PPRA) in the Kurikulum Merdeka. The research question of this study is to identify the similarities and differences between these two approaches in terms of the roles of teachers, the roles of families, and the learning approaches. The research method used is library research, by reviewing various relevant literature sources, including the works of Syekh Nawawi, curriculum documents of Kurikulum Merdeka and related studies by various authors. The review procedure was conducted by collecting and analyzing data from books, articles, and journals that explain Syekh Nawawi's views on moral education, as well as the concepts and implementation of character education in Kurikulum Merdeka. The literature reviewed includes Syekh Nawawi's works such as “Marah Labib" and Nashaikhul 'Ibad" official documents from the Ministry of Education, Culture, Research, and Technology and the Ministry of Religious Affairs of the Republic of Indonesia on the implementation of character education in P3 and PPRA, as well as other supporting literature. The conclusion of this study shows that both approaches have the same goal of developing the character and morals of students holistically. The main similarity is the emphasis on moral and religious values as the basis of education. The difference lies in the active role of teachers and families in education according to Syekh Nawawi, and the independent and student-centered approach in P3 and PPRA. Nawawi also emphasizes the integration of local culture and the Syafi'iyah school of thought in the learning materials, while P3 and PPRA emphasize the relevance of the cultural and environmental context of the students in general.  Abstrak Penelitian ini bertujuan untuk membandingkan pendidikan akhlak menurut Syekh Nawawi dengan pendidikan karakter dalam proyek penguatan Profil Pelajar Pancasila (P3) dan Profil Pelajar Rahmatan lil ‘Alamin (PPRA) dalam Kurikulum Merdeka. Rumusan masalah dalam penelitian ini adalah bagaimana persamaan dan perbedaan antara kedua pendekatan tersebut dalam hal peran guru, peran keluarga, dan pendekatan pembelajaran. Metode penelitian yang digunakan adalah kajian pustaka (library research), dengan menelaah berbagai sumber literatur yang relevan, termasuk karya-karya Syekh Nawawi, dokumen Kurikulum Merdeka, serta penelitian terkait dari berbagai penulis. Prosedur kajian dilakukan dengan mengumpulkan dan menganalisis data dari buku, artikel, dan jurnal yang memaparkan pandangan Syekh Nawawi mengenai pendidikan akhlak, serta konsep dan implementasi pendidikan karakter dalam Kurikulum Merdeka. Sumber pustaka yang dikaji meliputi karya Syekh Nawawi seperti kitab Marah Labib, Nashaikhul ‘Ibad, dokumen resmi Kemendikbudristek dan Kemenag Republik Indonesia tentang implementasi pendidikan karakter dalam P3 dan PPRA, serta literatur pendukung lainya. Kesimpulan dari penelitian ini menunjukkan bahwa kedua pendekatan tersebut memiliki tujuan yang sama dalam mengembangkan karakter dan akhlak peserta didik secara holistik. Persamaan utama adalah penekanan pada nilai-nilai moral dan religius sebagai dasar pendidikan. Perbedaan terletak pada peran aktif guru dan keluarga dalam pendidikan menurut Syekh Nawawi, serta pendekatan mandiri dan student-centered dalam P3 dan PPRA. Nawawi juga lebih mengutamakan integrasi budaya lokal dan pandangan madzhab syafi’iyah dalam materi pelajaran, sementara P3 dan PPRA menekankan relevansi konteks budaya dan lingkungan peserta didik secara umum.